Effect of temperature and salt/alcohol on the interaction of tetradecyltrimethylammonium bromide/Triton X-100 with moxifloxacin hydrochloride: A multitechnique approach - Aktar, Shahina; Robel Molla, Mohammad; Mahbub, Shamim; Abdul Rub, Malik; Hoque, Md. Anamul; Islam, D. M. Shafiqul (Journal of dispersion science and technology, 2019)
Interaction of moxifloxacin hydrochloride (MFH) with tetradecyltrimethylammonium bromide (TTAB) along with Triton X-100 (TX-100) under different experimental conditions has been carried out using multiple physico-chemical techniques. The micellar parameters like critical micelle concentration (cmc), counter ion binding (β), thermodynamic parameters such as , , and etc. associated with the drug-TTAB interaction have been determined. The changes of the values of cmc of TTAB by the addition of drug indicate the existence of TTAB-MFH interaction. The cmc values of drug-TTAB systems were found to be dependent on the variation of temperature, salt and alcohol concentrations. In all the cases the negative values of indicated the spontaneous micelle formation of drug-TTAB system. The values of and reveal the existence of hydrophobic and electrostatic interactions between drug and TTAB. The CP values of TX-100 in water were increased in the presence of MFH. The values of of drug-TX-100 mixed system are found to be positive which indicates the clouding process is nonspontaneous in nature. The binding constant (K b ) value for MFH-TX-100 system was found to be temperature dependent and the binding interaction between MFH and TX-100 is mainly due to hydrogen bonding.